Syrian and Lebanese Patricios in Sao Paulo : From the Levant to Brazil - Truzzi, Oswaldo (Book collections on Project MUSE., 2018)
"This project is a translation into English of a book by Oswaldo Truzzi on Syrians and Lebanese in São Paulo from the end of the 19th century to the 1950s. Truzzi begins by describing migrants' reasons for emigrating to Brazil. He examines the economic trajectory of many of the immigrants, from peddlers to retailers, wholesale traders, and industrialists, and discusses their efforts to reinvent the unfavorable identity of "merchant" by relating it to a strong work ethic and to a mission of spreading the novelties of progress (the merchandises they commercialized) to the farthest corners of Brazil. Truzzi considers the process of differentiation within the group, both economically and in terms of religious and ethnic affinities (particularly the perception of differences between Syrians and Lebanese), and discusses the professional aspirations of the second generation. He also undertakes a comparative discussion of Syrians and Lebanese in Brazil and the United States, noting the importance of pioneering commercial activities in haberdashery, clothing, and textile sectors, a niche dominated by Jews in the United States that Syrians and Lebanese pioneered in Brazil. The book closes with a discussion of a more recent wave of Lebanese Muslims migrants to São Paulo beginning in the 1960s"--